Extreme lattices: symmetries and decorrelation. (10th November 2016) - Andreanov, A; Scardicchio, A; Torquato, S
Abstract: We study statistical and structural properties of extreme lattices, which are the local minima in the density landscape of lattice sphere packings in d -dimensional Euclidean space R d . Specifically, we ascertain statistics of the densities and kissing numbers as well as the numbers of distinct symmetries of the packings for dimensions 8 through 13 using the stochastic Voronoi algorithm. The extreme lattices in a fixed dimension of space d ( d ⩾ 8 ) are dominated by typical lattices that have similar packing properties, such as packing densities and kissing numbers, while the best and the worst packers are in the long tails of the distribution of the extreme lattices. We also study the validity of the recently proposed decorrelation principle, which has important implications for sphere packings in general. The degree to which extreme-lattice packings decorrelate as well as how decorrelation is related to the packing density and symmetry of the lattices as the space dimension increases is also investigated. We find that the extreme lattices decorrelate with increasing dimension, while the least symmetric lattices decorrelate faster.